2022
DOI: 10.18632/aging.204098
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub biomarkers and immune cell infiltration in polymyositis and dermatomyositis

Abstract: Objective: Polymyositis (PM) and dermatomyositis (DM) are heterogeneous disorders. However, the etiology of PM/DM development has not been thoroughly clarified. Methods: Gene expression data of PM/DM were obtained from Gene Expression Omnibus. We used robust rank aggregation (RRA) to identify differentially expressed genes (DEGs). Gene Ontology functional enrichment and pathway analyses were used to investigate potential functions of the DEGs. Weighted gene co-expression network analysis (WGCNA) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…This duality in function extends to their participation in antiviral immunity and the regulation of cellular proliferation and immune activity [ 14 ]. Our findings are in alignment with Si Chen et al's analysis, which also identified IRF9 and hub genes within the IFN pathway, such as TRIM22, IFI6, IFITM1, and IFI35, as noteworthy players in PM pathogenesis [ 15 ]. Additionally, Tournadre A and colleagues observed that IFN-I secretion led to an upsurge in HLA-I gene expression [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…This duality in function extends to their participation in antiviral immunity and the regulation of cellular proliferation and immune activity [ 14 ]. Our findings are in alignment with Si Chen et al's analysis, which also identified IRF9 and hub genes within the IFN pathway, such as TRIM22, IFI6, IFITM1, and IFI35, as noteworthy players in PM pathogenesis [ 15 ]. Additionally, Tournadre A and colleagues observed that IFN-I secretion led to an upsurge in HLA-I gene expression [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, all these genes are involved in the immune response to virus infections and the type I interferon (IFN) signalling pathway. Chen et al confirmed the role of IFI16 as a putative hub gene in DM and polymyositis (PM) and identified four other putative hubs (TRIM22, IFITM1, IFI35, and IRF9) (4). Similar results were found in studies looking for IBM marker genes (5).…”
Section: Pathogenesismentioning
confidence: 55%
“…Idiopathic inflammatory myopathies: one year in review 2022 E. Dourado 1 , F. Bottazzi 2,3 , C. Cardelli 4,5 , E. Conticini 6 , J. Schmidt 7 , L. Cavagna 2,3 , S. Barsotti 4,8 Idiopathic inflammatory myopathies: one year in review 2022 / E. Dourado et al…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, LAP3 contributes to the depletion of arginine induced by IFN-γ in a bovine mammary epithelial cell model ( Li et al, 2022 ). While only one study has identified an upregulation in LAP3 expression within DM ( Chen et al, 2022 ), the exact underlying mechanism remains to be elucidated. In DM, a disease with significant mitochondrial dysfunction, patients exhibit a notable reduction in aerobic capacity with histopathological and biochemical evidence supporting the presence of OXPHOS dysfunction, particularly in the perifascicular regions ( Woo et al, 1988a ; Cea et al, 2002 ; Alhatou et al, 2004 ; Varadhachary et al, 2010 ; Meyer et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%